DAMPAK PENERAPAN PERNYATAAN STANDAR AKUNTANSI KEUANGAN (PSAK 68) TENTANG PENGUKURAN NILAI WAJAR TERHADAP PAJAK PENGHASILAN (STUDI KASUS PADA PT ASTRA INTERNATIONAL Tbk.) - Andi Marlinah (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2017)
The Title of this research is “The Impact of Statement of Financial Accounting Standards (PSAK 68) about Fair Value Measurement of the Income Tax (A Case Study on PT Astra International Tbk.)”., The presence of PSAK 68 give a effect to several reasons, among them income or comprehensive income, and also on taxation. The Focus of this research is about how a draft judgment in this case fair value measurement affect the income tax, both from the corresponding expenditures as well as regulations issued by the tax authority. The Method of this research is descriptive qualitative analysis. Data obtained from the official website of PT Astra International Tbk. which in turn stated that based on the three post which were analyzed by a researcher, found two of them to give effect to income tax based on the fair value measurement namely: (a) loss on the translation of receivables, and (b) exchange difference on translation of financial statements in foreign currencies. The next (c) revaluation of fixed assets, is based on the results of reseacrh that not give effect to income tax.